Just in Case You Ever Wonder - Lucado, Max; Tharlet, Eve (Nashville, Tennessee : Thomas Nelson,c[2019], 2019)
"This book assures children of God's love through all their experiences--including during hard times such as being afraid of the dark or being bullied--and gives assurance that the parent was there when they were first born and will be with them even in Heaven"--Provided by publisher.
Keywords: Parent and child -- Juvenile fiction; Christian life -- Juvenile fiction; Bears -- Juvenile fiction; Parent and child -- Fiction; Christian life -- Fiction; Bears -- Fiction; Picture books